HOW TO CRITICALLY APPRAISE A RESEARCH PAPER? - Ahmed, Ishtiaq (International Journal of Research -GRANTHAALAYAH, 2021)
Background: Critical appraisal of research paper is a fundamental skill in modern medical practice, which is skills-set and developed throughout the professional career. The professional experience facilitates this and through integration with clinical experience and patient preference, permits high quality evidence-based medicine practice in patient care. These skills to be mastered not only by academic medical professionals but also by the clinicians involved in clinical practice. Objective: To provide a simple and robust method for assessing the trustworthiness of a research paper and its value in clinical practice. Methodology: Through detailed literature search, All essential sections and subsection mandatory for a research paper were identified followed by the necessary steps or information required in each section or questions which may arise or needs to addressed were identified. The important questions or steps which are integral in assessing the reliability and validity of a research are gathered during critical review of a research paper. Results: Out of 128 full text articles, 49 full-text articles containing robust and pertinent information as per objective were short listed for review. Conclusion: Critical appraisal of a research paper or project is a fundamental skill in modern medical practice for assessing the worth of clinical research and in providing a guideline of its relevance to the profession.